NURSES' UNDERSTANDING OF THE EXERCISING OF LEADERSHIP IN THE HOSPITAL ENVIRONMENT - Simone Coelho Amestoy; Vânia Marli Schubert Backes; Letícia de Lima Trindade; Veridiana Corrêa Ávila; Anelise Freitas Lins de Oliveira; Camila Neves da Silva (Universidade Federal do Paraná, 2014)
This study aimed to investigate nurses' understanding regarding leadership, as well as the strategies used for facilitating its exercising in the hospital environment. It is research with a qualitative approach of the descriptive type, in which the case study was used as the investigative strategy. The participants were 25 nurses who worked in hospitals in Florianópolis, in the Brazilian state of Santa Catarina. The information were obtained between May and December 2010, through semi-structured interviews and dialogic workshops, and were analyzed using Thematic Analysis, with two themes emerging: 'The nurses' understanding regarding leadership', and 'Strategies which facilitate the exercising of leadership'. The results indicate that leadership is a relational skill which contributes to the management of the care, the team, and the hospital environment, being strengthened by dialogue as the main strategy facilitating and strengthening the exercising of the nurse's leadership.